Kegiatan Eco Print Pada Para Ibu-Ibu Kader Di Desa Sumber Sari Kecamatan Kabawetan Kabupaten Kepahiang - Aulia, Ebik; Pratama, Cindi; Rizki, Kemas; Rayani, Desma; Darmawansyah, Darmawansyah; Febriani, Emi; Rohani, Tuti; Azissah, Danur (Universitas Dehasen Bengkulu, 2025)
Introduction : The eco print activity organized by students from the Faculty of Health Sciences, Universitas Dehasen Bengkulu, in Sumber Sari Village, Kabawetan District, Kepahiang Regency, aims to empower local mothers through training in handmade crafts using organic plants. This activity is part of the Community Service Program (KKN) and is expected to increase knowledge of environmental health and the development of small and medium-sized enterprises (SMEs). Objective : The objective of this activity is to train the village's mothers in creating eco print crafts, enhance their creativity, and introduce the utilization of natural resources and the management of SMEs with a focus on digital marketing. Method : The training was held on January 27, 2025, at Posko 1 Dusun 3, Sumber Sari Village, using a demonstration method. Participants were provided with canvas bags and plant materials to create eco print designs, which were then soaked in alum water to enhance the results. Results and Discussion : The results of the activity showed an increase in local mothers' knowledge in several key areas. First, they gained a better understanding of managing SMEs with digital marketing as a means of promoting eco print products. Second, the mothers appreciated eco print as a form of therapeutic activity and relaxation, helping to reduce stress. Third, they gained a deeper understanding of utilizing natural resources as raw materials for eco print crafts. Finally, their skills and creativity in making eco print crafts improved, opening opportunities for the development of locally-based creative SMEs in Sumber Sari Village.